2010
DOI: 10.1080/03670244.2010.507440
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in the Food Environment and the Experience of Food Insecurity among Refugees Resettled in the United States

Abstract: The objective of this cross-sectional study was to assess the prevalence and correlates of food insecurity in 281 refugees resettled in the United States. Participants were recruited through a resettlement center and word of mouth. In addition to measures of socioeconomic status, education, time in the U.S., and food insecurity, we also measured individual difficulty in navigating the food environment using a food difficulty scale. Only 23% of the sample did not endorse any of the food insecurity items. Nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 27 publications
4
81
1
Order By: Relevance
“…These studies indicated low income, low education, low acculturation, shorter length of time in the United States, and language barriers as major factors leading to food insecurity among refugees. Further, refugees lacking knowledge about food outlet locations were 2.5 times more likely to report food insecurity (26). Depression was also associated with food insecurity among refugees (18).…”
Section: Research Methods and Assessment Of Dietary Intakementioning
confidence: 88%
See 3 more Smart Citations
“…These studies indicated low income, low education, low acculturation, shorter length of time in the United States, and language barriers as major factors leading to food insecurity among refugees. Further, refugees lacking knowledge about food outlet locations were 2.5 times more likely to report food insecurity (26). Depression was also associated with food insecurity among refugees (18).…”
Section: Research Methods and Assessment Of Dietary Intakementioning
confidence: 88%
“…In a study of Liberian refugees, child hunger was most likely to be present in households in which mothers reported difficulty navigating and understanding the American food environment (29). In addition, 63% of refugees reported not knowing how to cook American foods, and 40% reported difficulties finding stores with desired foods (26). Nevertheless, the level of difficulty in adapting to the US food environment was inconsistent across studies and refugee groups.…”
Section: Research Methods and Assessment Of Dietary Intakementioning
confidence: 99%
See 2 more Smart Citations
“…There are indications that there may be specific challenges related to this phase (Burns 2004;Dean et al 2010;Delavari et al 2012;Himmelgreen et al 2007;Mellin-Olsen and Wandel 2005;Newbold 2009;Tuomainen 2009). Unavailability or high prices of food used in traditional diets, limited information about shopping and cooking options, and changes in lifestyle and working conditions may result in dietary modifications that have an impact on health and food security (Donkin and Dowler 2002;Hadley, Patil, and Nahayo 2010;Mellin-Olsen and Wandel 2005;Sellen, Tedstone, and Frize 2002;Shaw 2009). Together with the lack of availability of familiar food, immigrants also face uncertainty about how to adapt their food habits to the new environment (Dean et al 2010;Himmelgreen et al 2007;Tuomainen 2009).…”
mentioning
confidence: 99%